Profile of postgraduate graduates from Costa Rican state universities who carry out research - Azofeifa Ureña, Cinthia (2025)
This article presents an analysis conducted to determine the profile of individuals who engage in research after completing postgraduate studies at Costa Rican public universities, as prior analyses identifying the main characteristics of researchers have not been developed. Additionally, the study aims to assess the contribution of postgraduate programs to research engagement and development in support of decision-making. The research follows a quantitative approach, utilizing data from the “Study of Postgraduate Graduates 2017-2019 from Public Universities,” collected in 2021 by the Consejo Nacional de Rectores. For the analysis, 1,240 postgraduate graduates involved in post-graduation research activities were selected. Hierarchical clustering techniques were applied to construct groups and profile the graduates engaged in research. Distances such as nearest neighbor, farthest neighbor, average linkage, and Ward’s distance were calculated to determine within-group similarities. Additionally, Gower's distance was employed to evaluate the distance among clustered research-engaged graduates. The findings reveal three distinct groups of postgraduate researchers, characterized primarily by language proficiency and their respective employment sectors.